Genetic profiling of locally registered Philippine coffee using molecular markers linked to resistance against diseases and pests - NICK RAINIER S. SANTOS; MONALIZA B. MAGAT; MIGUEL V. MONDRAGON; ERNELEA P. CAO; DAISY MAY C. SANTOS (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Santos NRS, Magat MB, Mondragon MV, Cao EP, Santos DMC. 2023. Genetic profiling of locally registered Philippine coffee using molecular markers linked to resistance against diseases and pests. Biodiversitas 24: 4136-4144. Coffee is a major commodity in the Philippines, but diseases and pests have hampered local production. Natural resistance could help increase production by eradicating infestation or lessening the symptoms of infection and minimizing the need for chemical control. Hence, this study aims to screen local Coffea arabica varieties, whose beans are prized for their superior taste and aroma, using genetic markers. These markers are linked to resistance against Coffee Leaf Rust (CLR, caused by Hemileia vastatrix), Coffee Berry Disease (CBD, caused by Colletotrichum kahawae), and Root Knot Nematode (RKN, Meloidogynespp.). The Arabica samples were obtained from the Bureau of Plant Industry in Baguio City, Benguet, a main distributor of coffee seedlings to farmers. C. canephora and C. liberica trees from Cavite State University, Indang, Cavite, were used as control samples. Results reveal that the registered NSIC-2008-Cf-A-05 (Red Bourbon) Arabica tree contains a unique haplotype in a region of chromosome 3. This region has been linked to the SH3 gene, which confers resistance against CLR, a promising result for infested areas. However, all Arabica samples are inferred to be susceptible to CBD and RKN. Hence, NSIC-2008-Cf-A-05 is a potential source for resistance genes specifically against CLR in future breeding programs.